The frequency of clinical signs in patients with fibromyalgia syndrome and the relationship between fibromyalgia syndrome and hypermobility [Fibromiyalji Sendromlu Hastalarda Klinik Belirtilerin Sikliǧi ve Fibromiyalji Sendromu-Hipermobilite ̇ Ilişkisi] - (:unkn) unknown (My University, 2004)
In this study, the objective was to evaluate the presence of hypermobility and the frequency of clinical signs in patients with fibromyalgia syndrome (FS). Fifty two women with a mean age of 42.6±9.7 years who had diagnosis of FS according to American College of Rheumatology criteria, were included in the study. The patients were questioned according to social and economical status, pain and other systemic complaints. Pain level was evaluated by visual analog scale (VAS) and hypermobility by using Beighton hypermobility criteria. 67.3% of the patients were married, 50% were housewife, and 75% women's economical level was medium. Mean duration of education and pain were 8.8±4.8 and 4.9±4.6 years, respectively. Mean VAS score was 7.2±1.7 cm. In the systemic evaluation, 96.2% of patients had fatigue, 76.9% had morning stiffness, and 69.2% had sleep disorder. In the Pearson linear correlation analysis; there was a negative correlation between VAS and economical level (r=-0.32; p=0.021). Unmarried FS patients had higher ratio of fatigue than others. Mean Beighton total score was 5.4±2.03 (0-9). In 81.4% of patients Beighton total score was ≥5 which could be interpreted as an association with hypermobility. We found a negative correlation between Beighton total score and age (r=- 0.45; p=0.02). As a result, it should be kept in mind that a majority of FS patients could have benign hypermobility.
Keywords: Beighton hypermobility criteria; Fibromyalgia syndrome; Hypermobility